Keterampilan Calon Guru SD Dalam Menerapkan Media Pembelajaran IPA Berbasis IT Terhadap Hasil Belajar Siswa SDN–5 Panarung Palangka Raya - Rita Rahmaniati (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
Problems in learning science (IPA) that occur to the students of SDN 5 Panarung Palangka Raya is the use of learning media that often done by the teacher but it has not been able to give the optimum results. It was signed by the students who can not follow the lesson well because they were tired, and do not have the braveness to argue or give a different idea according to the views and understanding that is in students themselves. This study is aimed to describe the skills of student teachers in implementing learning media based IT. The indicators to measure the achievement of the study conducted by using the principles of qualitative research. The results showed that the implementation of learning by students teacher in SD by using media based IT with the good category with an average score of 3.05. Students’ activity during the learning with media based IT is categorized well on the activity of carrying out the assignment that given by teacher (29.5%). Learning by using learning media based IT can improve students’ learning outcomes. It showed that the learning had been centered to the students.